Identification of Prone Areas of Soil Erosion Using Modified Morphometric Prioritization and Sediment Production Rate (Case Study of Kamyaran Basin) - mansor parvin (تحقیقات کاربردی علوم جغرافیایی)
Semi-arid watersheds are sensitive to soil erosion process and suffer considerable losses each year. Morphometric studies are an important method for identifying susceptible erosion zones and are a prerequisite for assessing erosion patterns in watersheds.The semi-arid Kamyaran basin is at risk of soil erosion due to lithological diversity, varied geomorphology, rugged topography and the nature-based livelihoods of its inhabitants and determination of soil erosion potential of this basin is essential for scientific management and sustainable development. The purpose of this study is to prioritize soil erosion potential in the Kamyaran basin. Methodologically, this research is based on WSA and averaging methods based on the calculation and ranking of morphometric parameters. The results showed that according to WSA methods and averaging 53.63% and 75.91% of Kamyaran catchment area, respectively, are located in areas with high soil erosion potential and require protection plans. The WSA method has better performance for prioritizing soil erosion studies due to different morphometric parameters and how to calculate it accurately. Sub-basins located in the northern areas of the Kamyaran Basin have high potential for soil erosion and sub-basins in the southern areas have low soil erosion potential. In general, the amount of soil erosion potential in Kamyaran basins is affected by the lithological and geomorphological conditions of the basins and the parameters related to infiltration have the most influence on the extent of soil erosion potential in the basins.